Mirabegron for Overactive Bladder: A Novel, First-in-Class ?3- Agonist Therapy - Imran, Mohammed; Najmi, Abul Kalam; Tabrez, Shams (Urology Journal, 2013)
Purpose: To discuss the pharmacotherapeutic aspects of Mirabegron which is a first-inclass novel β3 receptor agonist drug recently approved by the food and drug administration (FDA) for the treatment of overactive bladder (OAB). Materials and Methods: We conducted a computerized search of the MEDLINE/PUBMED databases with the word Mirabegron, β3 receptor agonist and overactive bladder. Results: Effect of Mirabegron on β3 adrenergic receptor purportedly releases nitric oxide (NO) by an increase in intracellular Ca2+ through accumulation of cyclic adenosine monophosphate (cAMP). Along with NO which relaxes the detrusor muscle, it also releases an urothelial-derived inhibiting factor (UDIF) that inhibits contractions. It increases the bladder capacity by causing bladder relaxation during the storage phase. Conclusion: Mirabegron appears to be a promising treatment in OAB patients by shifting its management from reducing detrusor over-activity to inducing relaxation. Also it lacks the troublesome side effects associated with the standard antimuscarinic management.